Ink‐Assisted Synthetic Strategy for Stable and Advanced Composite Electrocatalysts with Single Fe Sites. Issue 52 (30th November 2020) - Zhang, Zhengyuan; Hao, Jinhui; Lu, Yahui; Xu, Yuqi; Li, Longhua; Shi, Weidong
Abstract: The oxygen evolution reaction is critical to the efficiency of many energy technologies that store renewable electricity in chemical form. However, the rational design of high‐performance and stable catalysts to drive this reaction remains a formidable challenge. Here, a facile ink‐assisted strategy to construct a series of stable and advanced composite electrocatalysts with single Fe sites for permitting seriously improved performance characteristics is reported. As revealed by a suit of characterization techniques and theoretical methods, the improved electrocatalytic performance and stability can be attributed to the unique coordination states of Fe in the form of distorted FeO4 C and the interfacial effect in the composite system that optimize and stabilize single Fe sites in changing to better configurations for intermediates adsorption. The findings provide a novel strategy to in‐depth understanding of practical guidelines for the electrocatalyst design for energy conversion devices. Abstract : An ink‐assisted synthetic strategy for stable and advanced composite electrocatalysts with single Fe sites based on iron gallic acid complex is successfully designed. The origin of seriously improved performance for electrocatalytic oxygen evolution reaction can be attributed to the unique distorted structure of the FeO4 C coordination and well‐defined interfacial effect in the NiS2 NS@FeO/C composite system.